2008
DOI: 10.1143/jpsjs.77sa.275
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Spin and Orbital Hall Effects ind- andf-Electron Systems

Abstract: We study the intrinsic spin Hall conductivity (SHC) and orbital Hall conductivity (OHC) in various d-and f -electron systems. The obtained SHC and OHC are much larger than that in semiconductors. The origin of these huge Hall effects is the "effective Aharonov-Bohm phase factor" induced by the atomic angular momentum with the aid of the atomic spin-orbit interaction. Huge SHC and OHC due to this mechanism is expected to be ubiquitous in multiorbital transition metal complexes, which will open the possibility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 14 publications
(17 reference statements)
0
42
0
Order By: Relevance
“…After KL, theories of the intrinsic AHE [12,13,14,15,16,17,18,19,20,21,22,23] and the intrinsic SHE [5,6,7,8,24,25,26] have been improved based on several specific theoretical models. Kontani and Yamada [15] studied the intrinsic AHE based on the periodic Anderson model by considering the SOI unperturbatively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After KL, theories of the intrinsic AHE [12,13,14,15,16,17,18,19,20,21,22,23] and the intrinsic SHE [5,6,7,8,24,25,26] have been improved based on several specific theoretical models. Kontani and Yamada [15] studied the intrinsic AHE based on the periodic Anderson model by considering the SOI unperturbatively.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, authors in ref. [7] presented the first report on the theoretical study of SHE in transition metal compound Sr 2 RuO 4 , which has no Dirac cone type dispersion at the Fermi level. They had found that the origin of the huge Hall effect is the "effective Aharonov-Bohm (AB) phase" induced by d-orbital degrees of freedom, which are absent in semiconductors and in graphene.…”
Section: Introductionmentioning
confidence: 99%
“…In ref. [3], we presented the first report on the theoretical study of the SHE in transition metals: They have shown that the anomalous velocity due to the atomic degrees of freedom gives rise to the large SHC comparable to the experimetal values. Therefore, analyses based on the multiorbital tight-binding model are indipensible to elucidate the origin of the huge SHC in transition metals.…”
Section: Introductionmentioning
confidence: 79%
“…′ sin k y cos k x is called the "anomalous velocity", which is the origin of the Hall effects [3,6]. Since v a x has the same symmetry as k y , v a x v y can remain finite after the k-summations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation